Application of Seft Therapy for Anxiety in Hemodialysis Patients at Gunung Jati Regional General Hospital, Cirebon City - Alawiyah, Aay; Syaripudin, Ahmad; Romadhon, Lili Wahyuni (INDOGENIUS, 2025)
Background and Objective: Chronic Kidney Disease (CKD) with hemodialysis therapy is a condition of chronic kidney dysfunction that requires regular blood filtration procedures to replace declining kidney function. The World Health Organization (WHO, 2020) reports that the global prevalence of Chronic Kidney Disease reaches 10% of the population, while the number of CKD patients undergoing hemodialysis is estimated at approximately 1.5 million worldwide, with an annual increase of 8%. Analyzing the application of Seft therapy on anxiety in chronic kidney failure patients undergoing hemodialysis in the hemodialysis room at RSD Gunung Jati Hospital in Cirebon City. Method: This study uses a descriptive approach based on the results of previous case studies. The instruments used were the palliative nursing care format and the Zung Self-Rating Anxiety Scale (ZSAS). Results: SEFT therapy was administered over three sessions according to the hemodialysis schedule, resulting in a reduction in anxiety levels among chronic kidney disease patients undergoing hemodialysis in the Hemodialysis Unit at RSD Gunung Jati Hospital in Cirebon City. Conclusion: The application of SEFT therapy has been proven to be beneficial in reducing anxiety levels in patients with chronic kidney failure undergoing hemodialysis procedures in the Hemodialysis Room of Gunung Jati Regional General Hospital, Cirebon City.